ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL MATEMATIKA KELAS X MIPA SMA N 1 SOLOK SELATAN - Dila Novita (Departemen Matematika, 2021)
The purpose of this research to describe and analyze students' mistakes based on the Kastolan stages in solving math problems for class X MIPA SMA N 1 Solok Selatan. The errors studied are based on the types of errors in the Kastolan stage which include conceptual errors, procedural errors and technical errors. The type of research is descriptive with the research subject as many as six students of class X MIPA 1 SMA N 1 Solok Selatan. Details of taking the subject are two subjects with high math ability, two subjects with moderate math ability, two subjects with low math ability. The results showed that (1) as many as 26.88% of students experienced conceptual errors due to students' misunderstanding, forgot concepts and did not use the formula correctly. (2) as many as 35.48% of students experienced procedural errors due to not rechecking the answers before they were collected and confusion about the next steps due to lack of understanding of the material. (3) as many as 37.64% of students experienced technical errors due to the lack of accuracy of students when solving absolute value test questions and the lack of enthusiasm of students so that they answered random test questions which resulted in students being wrong in solving questions. Keywords – Analysis of Student Errors, Errors According to Kastolan Stages, Conceptual Errors, Procedural Errors, Technical Errors.